Complexo Carajás, Amazônia: as pretensiosas pegadas urbanizadoras de um território - Trevisan, Ricardo; Buiate Brandão, Simone; Rocha Reis, Talita; Guida Teixeira, Carolina; Botelho Trindade Vilela, Nádia; Nóbrega Queiroz de Paiva, Leonardo (Pontificia Universidad Católica del Perú, 2025)
In Brazil, the geopolitics adopted by the military government between 1964 and 1985 drove numerous actions and plans that promoted, among other fronts, the urbanization of the territory. In the state of Pará, the discovery in Serra dos Carajás (Carajás Mountains) of the largest iron ore reserve aroused the interest of foreign companies in the 1960s. As a support for the large-scale mineral exploration, a logistical contribution was necessary, promoting the implementation of infrastructure and the expansion or creation of urban centers. By consulting existing sources and documents, the history of this territory is revealed, pointing out and discussing the changes it has undergone in the last 50 years.

No Brasil, a geopolítica adotada pelo governo militar entre 1964 e 1985 impulsionou diversas ações e planos que, entre outras frentes, promoveram a urbanização do território. No estado do Pará, a descoberta da maior reserva de ferro, localizada na Serra dos Carajás, despertou o interesse de empresas estrangeiras na década de 1960. Para viabilizar a exploração mineral em larga escala, foi necessário um aporte logístico que incentivou a implantação de infraestruturas e a expansão ou criação de núcleos urbanos. A partir da consulta a fontes e documentos existentes, este estudo revela a história deste território, destacando e discutindo as mudanças ocorridas nos últimos 50 anos.
Complexo Carajás, Amazônia: the pretentious urbanizing footprints of a territory
Keywords: Company towns; Territory; Infrastructure; Urban network; New cities; Ciudades empresa; Territorio; Infraestructura; Red urbana; Nuevas ciudades; Cidade empresarial; Território; Infraestrutura; Rede Urbana; Cidades Novas; https://purl.org/pe-repo/ocde/ford#6.04.08